2010
DOI: 10.1038/aja.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

Reference limits: limited references in laboratories worldwide

Abstract: The newly revised World Health Organization (WHO) semen analysis manual provides the lower refe rence limits of semen parameters based on "the raw data from between about 400 and 1 900 semen samples, from recent fathers in eight countries on three continents": Australia, Europe and North America [1]. The other continents, Asia, Africa, and South America, and most regions of the above three continents, such as southern Europe, were not represented in the raw data used to generate the reference limits. To my kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Povey et al (2012) reported that Black ethnicity was a risk factor for low motile sperm concentration in a case-control study of male partners of infertile couples. Huang, 2010 noted that current WHO reference ranges are based on men living in Australia, Europe and North America and that data on semen parameters in fertile men living outside these continents are lacking and that the possibility of ethnic differences should be considered in establishing reference ranges. As the number of Black men in our study was relatively small compared with White or Hispanic/Latino men, these results should be viewed as preliminary, but worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Povey et al (2012) reported that Black ethnicity was a risk factor for low motile sperm concentration in a case-control study of male partners of infertile couples. Huang, 2010 noted that current WHO reference ranges are based on men living in Australia, Europe and North America and that data on semen parameters in fertile men living outside these continents are lacking and that the possibility of ethnic differences should be considered in establishing reference ranges. As the number of Black men in our study was relatively small compared with White or Hispanic/Latino men, these results should be viewed as preliminary, but worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Semen quality has received attention from different professional disciplines. Since a decline in male semen quality was first reported in the 1990s, countries, regions and ethnic groups have continued to pay attention to changes in male semen parameters in their own populations (Elbardisi et al 2018;Glazer et al 2019;Huang 2010;Redmon et al 2013). Although the findings have been inconsistent from time period to time period and from region to region, the focus on semen parameters has not diminished.…”
Section: Discussionmentioning
confidence: 99%